Aminoguanidine impedes human pancreatic tumor growth and metastasis development in nude mice - Mohamad, Nora Alicia (2009)
Aim: To study the action of aminoguanidine on pancreatic cancer xenografts in relation to cell proliferation, apoptosis, redox status and vascularization. Methods: Xenografts of PANC-1 cells were developed in nude mice. The animals were separated into two groups: control and aminoguanidine treated. Tumor growth, survival and appearance of metastases were determined in vivo in both groups. Tumors were excised and ex vivo histochemical studies were performed. Cell growth was assessed by Ki-67 expression. Apoptosis was studied by intratumoral expression of B cell lymphoma-2 protein (Bcl-2) family proteins and Terminal deoxynucleotidyl transferase biotin-dUTP Nick End Labeling (Tunel). Redox status was evaluated by the expression of endothelial nitric oxide synthase (eNOS), catalase, copper-zinc superoxide dismutase (CuZnSOD), manganese superoxide dismutase (MnSOD) and glutathione peroxidase (GPx). Finally, vascularization was determined by Massons trichromic staining, and by VEGF and CD34 expression. Results: Tumor volumes after 32 d of treatment by aminoguanidine (AG) were significantly lower than in control mice (P < 0.01). Median survival of AG mice was significantly greater than control animals (P < 0.01). The appearance of both homolateral and contralateral palpable metastases was significantly delayed in AG group. Apoptotic cells, intratumoral vascularization (trichromic stain) and the expression of Ki-67, Bax, eNOS, CD34, VEGF, catalase, CuZnSOD and MnSOD were diminished in AG treated mice (P < 0.01), while the expression of Bcl-2 and GPx did not change. Conclusion: The antitumoral action of aminoguanidine is associated with decreased cell proliferation, reduced angiogenesis, and reduced expression of antioxidant enzymes.